A Universal Photochemical Approach to Ultra‐Small, Well‐Dispersed Nanoparticle/Reduced Graphene Oxide Hybrids with Enhanced Nonlinear Optical Properties. Issue 6 (16th February 2015) - Tan, Dezhi; Liu, Xiaofeng; Dai, Ye; Ma, Guohong; Meunier, Michel; Qiu, Jianrong
<x xml:space="preserve">Abstract</x> Integrating multiple functionalities into individual nanoscale hybrids with strong nonlinear optical (NLO) response to ultrafast laser pulses is of tremendous importance. Here, a series of ultra‐small and well‐dispersed nanoparticles (NPs) supported on the undoped and doped reduced graphene oxide (rGO) are obtained via a general and versatile photochemical technique. Extremely fast heterogeneous nucleation rate and cooling rate having negligible thermal effect induced by a femtosecond laser are proposed to play a determined role in the formation of ultra‐small NPs. No surfactants, reduction reagents, or toxic materials are needed. The prepared rGO hybrids exhibit significantly enhanced ultrafast NLO response with very low optical limiting threshold, which originates from the fast and efficient electron and/or energy transfer from ultra‐small NPs to rGO. This study may represent an important universal step toward the generation of graphene hybrid nanostructures and even complex 3D functional systems consisting of multiple functional ultra‐small subunits with new horizons for numerous applications, especially in ultrafast nonlinear optics.